Business and sustainability concepts, strategies and changes - Eweje, Gabriel; Perry, Martin, 1956- (Emerald, 2011)
In recent years research on business and sustainability, particular attention is being given to the motivations driving business managers to incorporate social and environmental strategies into their day-to-day business activities. Such research is critical to the evaluation of green management whether viewed from the perspective of academics, managers, policy makers or business students. This volume aims to assist readers to navigate the conceptual maze surrounding discussions of business and sustainability by offering critical reflection on the state of business action for environmental sustainability and providing evidence about what is actually taking place in real localities and businesses. The chapters in the volume are focusing on sustainability issues that are critical, topical, and needed at this stage of the discussion. The volume makes three main contributions. First, it offers a critical review of business engagement with sustainability from four perspectives: sustainability as a political project; sustainability as a response to environmental crisis, sustainability as business opportunity and sustainability as stakeholder management. Second, the volume examines actual experience in terms of the steps being taken by business and how these have affected business performance. Third, the volume provides case studies of individual organizations or institutions that reveal tensions and challenges to progressing sustainable business strategies and that offer insight into the prospects for changing the relationship of business to the environment.
Keywords: Social responsibility of business.; Sustainable development.; elektronické knihy; electronic books